2010
DOI: 10.1029/2010gl042679
|View full text |Cite
|
Sign up to set email alerts
|

Lightning response to smoke from Amazonian fires

Abstract: [1] The effect of anthropogenic aerosols on clouds has the potential to be a key component for climate change predictions, yet is one of the least understood. It is possible that high aerosol loading can change the convection intensity and hence the electrical activity of thunderstorm clouds. Focusing on the Amazon dry season, where thousands of man-made forest fires inject smoke into the atmosphere, we studied the aerosol effects on thunderclouds. We used the ground-based World-Wide Lightning Location Network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
112
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 36 publications
(39 reference statements)
14
112
0
2
Order By: Relevance
“…The previous studies [55] indicated that lightning activity is linked closely with the cloud top height, and the flash rate increases with the cloud height as a power law. The results (Figures 3 and 4) are consistent with the previous studies of Altaratz et al [28] which discussed the effects of smoke aerosol loading on the convection intensity and lightning activities of thunderstorms over the Amazon by using World-Wide Lightning Location Network (WWLLN) lightning data and MODIS cloud and aerosol data. They found that the clouds with a higher cloud top height and larger cloud coverage are closely associated with stronger convection and electrical activity.…”
Section: Relationships Between Lightning Density and Cloud Propertiessupporting
confidence: 82%
See 2 more Smart Citations
“…The previous studies [55] indicated that lightning activity is linked closely with the cloud top height, and the flash rate increases with the cloud height as a power law. The results (Figures 3 and 4) are consistent with the previous studies of Altaratz et al [28] which discussed the effects of smoke aerosol loading on the convection intensity and lightning activities of thunderstorms over the Amazon by using World-Wide Lightning Location Network (WWLLN) lightning data and MODIS cloud and aerosol data. They found that the clouds with a higher cloud top height and larger cloud coverage are closely associated with stronger convection and electrical activity.…”
Section: Relationships Between Lightning Density and Cloud Propertiessupporting
confidence: 82%
“…One of them is the indirect microphysical effect that inspires the intensity of the convective cloud and the electrical activity. The inverse aspect is the direct radiative effect that suppresses the development of convection and the production of lightning [24,28]. The complex physical processes of the aerosol effect on clouds result in the uncertainty of the aerosol effect on electrical activity.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flash rates are correlated with numerous meteorological variables, including surface temperature [Price, 1993;Williams and Stanfill, 2002;Markson, 2007], convective available potential energy (CAPE) [Rutledge et al, 1992], cloud top height [Price and Rind, 1992;Price et al, 1997], cold-cloud depth [Futyan and Del Genio, 2007;Yoshida et al, 2009], convective precipitation [Meijer et al, 2001], upper tropospheric convective mass flux , integrated convective mass flux [Deierling et al, 2005], updraft vertical velocity or volume Barthe et al, 2010], precipitation ice mass, path, or flux Barthe et al, 2010], and aerosol concentration [Michalon et al, 1999;Andreae et al, 2004;Altaratz et al, 2010;Yuan et al, 2011].…”
Section: Appendix A: Lightning Parameterizationmentioning
confidence: 99%
“…Observational studies [4][5][6][7][8][9] have indicated that anthropogenic aerosol particles produced from metropolitan regions, highways, and factories increase the intensity of thunderstorms, and the density and frequency of lightning. The emission of smoke from forest fires also has a marked impact on the electric processes of thunderstorms, leading to an increase in lightning activity around and downwind of forest regions, an increase in the percentage of positive cloud-to-ground lighting flashes, and a reduction in the percentage of negative cloud-to-ground lighting flashes [10][11][12][13]. 2 of 19 Aerosol particles influence the electrification processes in thunderstorms by influencing liquid water and ice-phase particles.…”
Section: Introductionmentioning
confidence: 99%